Diagnosis of factors affecting the strategic implementation of sewage projects ( Case study in General Directorate of sewage projects ) - الكبيسي صلاح الدين عواد; مهدي اسامة محمود (Journal of Economics and Administrative Sciences, 2019)
This Research aim to identify the factors affecting the strategic implementation of sewage projects and to seek to activate the real follow-up of projects to identify the factors that accompany their implementation, The study included a sample of the projects of the investment plan implemented for the Directorate General of sewage in the governorates of Iraq, which was completed during the six years period (2010-2016). The sample of the research was four projects: The project of implementation and processing of the treatment plant and the lifting station and the conveyor line for the project of IMARA/The third stage/Al-Sanaf marshland , The project of the processing and implementation of the treatment plant with the carrier line in the IMARA / the second stage / Al-Bitira, the project of the implementation and installation of sewerage systems with the holy lifting station / Karbala and the project of processing and implementation of the treatment plant with 2 lift stations and conveyor line in Wasit / Azizia, A case study to collect information For these projects through the planning and follow-up department and the implementation section in the Directorate General of sewerage as well as "personal interviews to reach the results, The researcher reached a number of results, the most important of which is that the project departments pay greater attention to the strategic factor and the organizational structure among the factors affecting the strategic implementation and to a lesser extent the shared values factor among the employees, and the lack of ownership of the public sewerage system to activate communication between departments of the department and project management in progress To accelerate the decision-making process and the exchange of information, which reflected on its ability to follow up and control , The researcher also made several recommendations, the most important of which is an extensive study of the priorities of the project by the committees based on implementation after the assignment of work immediately and before the commencement and each according to its competence.